MicroRNA367 negatively regulates the inflammatory response of microglia by targeting IRAK4 in intracerebral hemorrhage - Yuan, Bangqing (J Neuroinflammation, 2015)
BACKGROUND: Intracerebral hemorrhage (ICH) induces microglial activation and the release of inflammatory cytokines, leading to inflammation in the brain. IRAK4, an essential component of the MyD88-dependent pathway, activates subsets of divergent signaling pathways in inflammation. METHODS: In the experiment, microglia were stimulated with erythrocyte lysates, and then miR-367, IRAK4, NF-ĸB activation and downstream proinflammatory mediator production were analyzed. In addition, inflammation, brain edema, and neurological functions in ICH mice were also assessed. RESULTS: Here, we report that ICH downregulated miR-367 expression but upregulated IRAK4 expression in primary microglia. We also demonstrate that miR-367 suppressed IRAK4 expression by directly binding its 3′-untranslated region. MiR-367 inhibited NF-ĸB activation and downstream proinflammatory mediator production. Knocking down IRAK4 in microglia significantly decreased the IRAK4 expression and inhibited the NF-ĸB activation and the downstream production of proinflammatory mediators. In addition, our results indicate that miR-367 could inhibit expression of proinflammatory cytokines, reduce brain edema, and improve neurological functions in ICH mice. CONCLUSIONS: In conclusion, our study demonstrates that miR-367/IRAK4 pathway plays an important role in microglial activation and neuroinflammation in ICH. Our finding also suggests that miR-367 might represent a potential therapeutic target for ICH.